The Role of Clinical-Morphological Genetic Factors in the Development and Course of Maxillary Sinus Cysts - Ismatovich, Muxiddinov Alisher; Abduqaxxorovich, Joʼrayev Jamol (American Journal of Bioscience and Clinical Integrity, 2025)
Frontal sinusitis is an inflammation of the mucous membrane of the frontal sinus. The main symptoms of the disease are headache with an epicenter in the eyebrow and spreading to the parietal and temporal regions, discharge of purulent or mucous exudate from the nose, intoxication syndrome and loss of smell. The diagnosis is based on the results of anamnesis, general examination, rhinoscopy, radiography or computed tomography and sinus endoscopy. The treatment program includes antibacterial drugs, detoxification therapy, nasal mucosal anemia, surgical drainage of the sinuses and physiotherapy procedures. In the etiology of acute inflammation of the frontal sinuses, acute respiratory viral infections caused by rhinoviruses, adenoviruses, coronaviruses or respiratory syncytial infections play a leading role. In chronic forms, the causative agent of the infection is most often bacteria - Moraxella catarrhalis and representatives of coccal microflora (Staphylococcus aureus, Streptococcus pneumoniae) in combination with Haemophilus influenzae. In rare cases, the causative agents are pneumococci, pseudodiphtheria bacillus, and pathogenic fungi. There are a number of factors that contribute to the development of frontal sinusitis.